Analisis Sentimen Terhadap Bantuan Subsidi Upah (BSU) pada Kenaikan Harga Bahan Bakar Minyak (BBM) - Ulfa Kurniasih; Akrim Teguh Suseno (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Fuel Oil (BBM) is a very important commodity for the people of Indonesia. The increase in fuel prices will have an impact on economic instability in Indonesia. Therefore, the government makes a policy by providing Wage Subsidy Assistance (BSU) to the community to ward off the impact of rising fuel prices. However, there were various responses from the public regarding the provision of BSU on the increase in fuel prices, especially on Twitter social media, some were supportive but some did not agree. This study aims to analyze the sentiments of the Indonesian people on government policies related to the provision of BSU to the increase in fuel prices. The data used are 795 tweets on each keyword BBM and BSU. The data is divided into 2, training data of 263 and 532 for testing data. The method used is classification with Naïve Bayes algorithm. The results of the analysis show that the BBM keyword positive sentiment is 28.2%, and negative sentiment is 71.8%. For BSU keywords, positive sentiment is 65.2% and negative sentiment is 34.8%. At the level of accuracy with this method, the result is 82.64% and the precision is 92.89%. Therefore, it can be concluded that the results of public sentiment towards the Wage Subsidy Assistance (BSU) received a positive response, while the increase in the price of fuel oil (BBM) received a negative response.